Short and Long-Term Effects of Anesthesia in Octopus maya (Cephalopoda, Octopodidae) Juveniles - Roumbedakis, Katina; Alexandre, Marina N.; Puch, José A.; Martins, Maurício L.; Pascual, Cristina; Rosas, Carlos (Frontiers in Physiology, 2020)
This study aimed to explore different substances (or cold sea water) as potential anaesthetic agents to facilitate short-term handling in Octopus maya juveniles. We investigate oxygen consumption before (baseline), during (first 10 min of exposure) and after anaesthesia (recovery) of octopuses exposed to cold sea water (SW; 11 and 13 oC), ethanol (EtOH; 0.5; 1.5 and 3.0%), magnesium chloride (MgCl2; 0.75; 1.5 and 3.75%), ethanol combined with magnesium chloride (Mix; 1.5:0.75%; 0.75:1.13% and 2.25:0.37%) and clove oil (0.15 mL L–1). After exposure, the animals were handled for 180 sec (exposed to air) and weighted. Two experimental groups not exposed to anaesthetics (with or without handling) were also evaluated. The criteria for general anaesthesia were analysed. Times of induction and recovery, incidence of attack response after recovery and possible longer-term effects of repeated general anaesthesia on cephalopods’ growth and mortality were evaluated. During anaesthesia, O. maya juveniles exposed to SW (11 and 13 oC), EtOH (0.5; 1.5 and 3.0%), Mix (0.75:1.13%), and clove oil, presented a significant decrease on oxygen consumption. In animals exposed to different concentrations of EtOH and Mix 0.75:1.13%, this decrease was registered after an increase on oxygen consumption. Animals exposed to MgCl2 did not show significant changes on oxygen consumption, except for animals exposed MgCl2 3.75%, which showed a significant increase on oxygen consumption. At the end of recovery, except for octopuses exposed to clove oil and MgCl2 0.75%, the values of oxygen consumption observed were comparable to the ones registered during baseline. Animals exposed to SW 11 oC, EtOH 3.0%, Mix 1.5:0.75% and MgCl2 3.75% fulfil the criteria defined for general anaesthesia. Exposure to MgCl2 (all concentrations), SW 13°C and clove oil reduced or inhibited the incidence of attack response. Except for animals exposed to clove oil, growth of the juveniles was not affected by the exposure to the different substances. Short-term handling (180 sec) of O. maya juveniles can eventually be carried out without anaesthesia. However, to facilitated handling, we suggest the use of EtOH 3.0% or cold sea water 11oC.